2017
DOI: 10.1002/ejp.1035
|View full text |Cite
|
Sign up to set email alerts
|

Placebo‐like analgesia via response imagery

Abstract: BackgroundPlacebo effects on pain are reliably observed in the literature. A core mechanism of these effects is response expectancies. Response expectancies can be formed by instructions, prior experiences and observation of others. Whether mental imagery of a response can also induce placebo‐like expectancy effects on pain has not yet been studied systematically.MethodsIn Study 1, 80 healthy participants were randomly allocated to (i) response imagery or (ii) control imagery. In Study 2, 135 healthy participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…In addition, mental representation techniques could contribute to the gradual extinction of the patterns of associative learning between pain and movement due to the activation of the neural mechanisms of movement, but without leading to the appearance of pain (Simons, Elman, & Borsook, ). Finally, several studies have reported that at the neurophysiological level, distraction caused by the mental practice might be associated with the generation of hypoalgesic effects (Hayashi, Aono, Shiro, & Ushida, ; Peerdeman, van Laarhoven, Bartels, Peters, & Evers, ). This process could be another variable underlying the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mental representation techniques could contribute to the gradual extinction of the patterns of associative learning between pain and movement due to the activation of the neural mechanisms of movement, but without leading to the appearance of pain (Simons, Elman, & Borsook, ). Finally, several studies have reported that at the neurophysiological level, distraction caused by the mental practice might be associated with the generation of hypoalgesic effects (Hayashi, Aono, Shiro, & Ushida, ; Peerdeman, van Laarhoven, Bartels, Peters, & Evers, ). This process could be another variable underlying the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Both acupuncture and imagery have long been used in medical practice, including the treatment of chronic pain [ 6 9 ]. However, the mechanisms that mediate acupuncture and imagery efficacy remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…First, this might be accomplished by influencing expectancies regarding the effectiveness of an intervention, i.e., outcome expectancies [ 18 , 20 ]. Prior studies have demonstrated the effectiveness of outcome expectancies induced by verbal suggestions in relieving itch and pain in healthy participants [ 21 , 22 ], and have shown that verbal suggestions are able to induce analgesic effects in various clinical patient populations, including patients with irritable bowel syndrome and patients undergoing thoracotomy [ 23 25 ]. A second way to influence health outcomes is by means of verbal suggestions that influence specific actions of approaching and avoiding certain stimuli without actually performing these actions, i.e., stimulus-response contingency instructions [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%